2020
DOI: 10.2298/sarh190322098v
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and correlates of depression at the primary health care level in Belgrade

Abstract: Introduction/Objective The prevalence of depression in primary care is relatively high. The aim of the study was to assess the frequency of depression among patients in Zvezdara Primary Health Care Center in Belgrade. We also examined the relationship between depression and individual risk factors (sociodemographics, lifestyle characteristics, and health-related factors). Methods A cross-sectional study, which included 422 adult patients, under 65 years of age, was conducted at the Zvezdara Primary Health Care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Depression and depressive disorders are often associated with numerous sociodemographic factors. A study conducted by Vučurević et al found an association between depression and marital status, employment, previous contact with mental health services, but above all with chronic illness [9]. Anxiety is experienced by all dialysis patients examined in a study conducted by Novaković et al in 2007 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Depression and depressive disorders are often associated with numerous sociodemographic factors. A study conducted by Vučurević et al found an association between depression and marital status, employment, previous contact with mental health services, but above all with chronic illness [9]. Anxiety is experienced by all dialysis patients examined in a study conducted by Novaković et al in 2007 [10].…”
Section: Introductionmentioning
confidence: 99%